The Role of Work Life Balance as a Mechanism for Employee Adaptation in Facing the Workload to Increase Human Resource Productivity at Bank Indonesia Representative Office in Bangka Belitung Islands Province - Asfari Rashifansyah; Andriyastuti Suratman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the role of work life balance as a mechanism for employee adaptation in dealing with workload to increase human resource productivity at the Bank Indonesia Representative Office in Bangka Belitung Islands Province. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation. The research informants consisted of five employees who were selected based on their tenure and work unit to gain diverse perspectives. Data analysis was carried out using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawn, with data validity tests through triangulation and member checking. The results showed that the workload of employees in general was in the controlled and proportional category, although in certain periods there was an increase in work intensity and time pressure. In dealing with these conditions, employees apply work-life balance as a form of adaptation through time management, determination of work priorities, and social support from leaders and colleagues. The implementation of time-balance, engagement, and satisfaction has been proven to help employees maintain focus, motivation, and quality of work. Thus, work-life balance plays an important role in maintaining the stability of human resource productivity despite fluctuations in workload. This research provides practical implications for organizations in formulating human resource management policies that are more oriented towards work-life balance to support sustainable performance.